Association Between Simian Virus 40 and Human Tumors - Rotondo, John Charles; Mazzoni, Elisa; Bononi, Ilaria; Tognon, Mauro; Martini, Fernanda (Frontiers in Oncology, 2019)
Simian virus 40 (SV40) is small DNA tumor virus of monkey origin. This polyomavirus was administered to human populations mainly through contaminated polio vaccines, which were produced in naturally-infected SV40 monkey cells. Previous molecular biology and recent immunological assays have indicated that SV40 is spreading in human populations, independently from early SV40-contaminated vaccines. SV40 DNA sequences have been detected at higher prevalence in specific human cancer specimens, such as brain and bone tumors, malignant pleural mesotheliomas and lymphoproliferative disorders, compared to corresponding normal tissue/specimens. However, other investigations, which reported negative data, did not confirm an association between SV40 and human tumors. To circumvent the controversies, which have arisen because of these molecular biology studies, immunological research with newly developed indirect ELISA tests were carried out in serum samples from patients affected by the same kind of tumors as mentioned above. These innovative indirect ELISAs employ synthetic peptides as mimotopes/specific SV40 antigens. SV40 mimotopes do not cross-react with the homologous human polyomaviruses, BKPyV and JCPyV. Immunological data obtained from indirect ELISAs, using SV40 mimotopes, used to analyze serum samples from oncological patients has indicated that these sera had a higher prevalence of antibodies against SV40 compared to healthy subjects. The main data on (i) the biology and genetics of SV40; (ii) the epidemiology of SV40 in the general population, (iii) the mechanisms of SV40 transformation; (iv) the putative role of SV40 in the onset/progression of specific human tumors, and (v) its association with other human diseases are reported in this review.